State of free-radical processes and antioxidant defence of patients with psoriasis and concomitant essential hypertension - V. A. Visir; G. I. Makurina (Zaporožskij Medicinskij Žurnal)
Objective: to study the status of free-radical processes and antioxidant protection parameters in patients with psoriasis and concomitant essential hypertension.